2023
DOI: 10.1186/s12879-023-08575-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of tuberculosis among people living with HIV/AIDS in China: a systematic review and meta-analysis

Cong-Cong Qi,
Li-Ran Xu,
Chang-Jia Zhao
et al.

Abstract: Objective To estimate the prevalence and risk factors associated with tuberculosis (TB) among people living with human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome (AIDS) in China. Methods A systematic review and meta-analysis were conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. After the literature was screened based on the inclusion and exclusion criteria, STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Most of the HIV/TB-co-infected patients had less than eight years of schooling and also had low incomes. This apparent association might have been a consequence of other health hazards, including the lack of health education and not having access to health care [23,24]. The study also showed that the majority (68.8%) of the participants with PTH were males, while 43 (60.6%) of the participants without PTB were females, with a p-value of 0.001 and an odds ratio of 0.48 (0.…”
Section: Pulmonary Tuberculosis Among Patients Living With Hiv/aidsmentioning
confidence: 82%
See 1 more Smart Citation
“…Most of the HIV/TB-co-infected patients had less than eight years of schooling and also had low incomes. This apparent association might have been a consequence of other health hazards, including the lack of health education and not having access to health care [23,24]. The study also showed that the majority (68.8%) of the participants with PTH were males, while 43 (60.6%) of the participants without PTB were females, with a p-value of 0.001 and an odds ratio of 0.48 (0.…”
Section: Pulmonary Tuberculosis Among Patients Living With Hiv/aidsmentioning
confidence: 82%
“…This could be because male gender is more associated with behaviours that could increase the risk of getting the disease than their female counterparts, such as drinking alcohol and smoking, among others, when compared with other studies. Qi et al, [24] Studies in southern Asia found that HIV-TB co-infection was diagnosed in 18.9% with a higher prevalence among males (75.3%), in the sexually active age group 31-45 years (61.3%), with less than primary education (44.15%), who were married (56.1%), laborers (42.4%), from rural backgrounds (88.2%), and having low income-earning capacity (94.4%). In addition, a study in Brazil also found that there are more men with registered cases of TB without HIV, at a ratio of 2:1 men to women [25].…”
Section: Pulmonary Tuberculosis Among Patients Living With Hiv/aidsmentioning
confidence: 99%
“…Also, males have poor health-seeking behaviour than females in our part of the country which may adversely impact their treatment adherence and outcomes. Several studies have also reported the lethal synergy between TB and HIV [7,[27][28][29][30][31]. In congruence, Amante and Ahemed [32] and Teketelew et al [20] demonstrated that younger age and Pulmonary negative TB cases were at significant risk of survival.…”
Section: Discussionmentioning
confidence: 98%
“…Among the most important global health challenges are infectious diseases such as tuberculosis (TB), acquired immunodeficiency syndrome, and human immunodeficiency virus infection [1,2]. Mycobacterium tuberculosis, an aerobic, Gram-positive, non-motile, acid-fast tubercular, rod-shaped bacillus, causes airborne TB, which mostly affects the lungs but may also impact extra-pulmonary regions [3].…”
Section: Introductionmentioning
confidence: 99%